Rancang Bangun Animasi Interaktif Berbasis Multimedia Pada Pengenalan Dasar Bahasa Jepang - Safitri Linawati; Siti Nurajizah (Computer Science (CO-SCIENCE), 2021)
The use of language as a medium of communication is currently important. Language is a way to communicate and interact with other people. Selain bahasa inggris yang menjadi bahasa  internasional, terdapat beberapa bahasa negara lain yang juga tidak kalah diminati untuk dipelajari, salah satunya adalah  bahasa jepang. Japanese language has a unique writing and pronunciation structure, so it takes persistence in learning it. However, the use of letters, sentence structure, and grammar structures that are different from Indonesian grammar makes it difficult for beginners to learn Japanese. The author tries to create an application that connects the multimedia functions on the computer with the knowledge of basic Japanese language introduction. In this study, using the waterfall software development method in making animation of basic Japanese language introduction. The result of this research is an animation that discusses the introduction of the country of Japan, the letters used in Japanese, greetings that are often used in everyday life, and how to introduce oneself in Japanese which is presented in the form of interactive animation so that it can help users. to understand basic Japanese.